Volatile Phenols—Important Contributors to the Aroma of Plant-Derived Foods - Schieber, Andreas; Wüst, Matthias (Molecules (Basel, Switzerland), 2020)
Volatile phenols like phenylpropanoid and benzoid compounds originate from the aromatic amino acid phenylalanine, which is biosynthesized via the shikimate/arogenate pathway. These volatile compounds contribute to the aroma of a number of economically important plant-derived foods like herbs, spices and fruits. The sequestration of numerous phenylpropanoid and benzoid compounds as glycosides occurs widely in fruits, and this pool represents an important source of flavor that can be released during storage and processing. Therefore, this review will provide an overview of the biosynthesis of free and glycosylated phenylpropanoid and benzoid compounds and their reactions during food processing, which both lead to the generation of odor-active volatile phenols in plant-derived foods.